واتای سیمانتیکی و پڕاگماتیکی گیرەکە وشەداڕێژەکان لە زمانی کوریدا - عومەر, پ.ی.د.نەوزاد ئەنوەر; صادق, م.سیدەوان عبداللە (Sulaimani Journal for Humanities, 2023)
drivationl morphemes are the form of own language, this form probably is more than meanings in it, it can change the shape and the meaning of the words and have basis, within use to the aim of fill in needs of language it's forming new words and phrases and they role important in the process of forming to produce in a new word. Undoubted drivational morphemes hold the concept and meaningful. Pursuant of appearing place and concept of the meaning made into several category of morphemes, to hold the shape and semantic meaning. The part of morphemes gave the pragmatic meaning except the semantic meaning thus known as the morphopragmatical. In this research the meaning of semantic meaning and pragmatic a part of drivation morpheme explain and declared.